Microwave sintering of Ni-Co doped barium strontium hexaferrite synthesized via sol-gel method - Kanagesan, Samikannu; Hashim, Mansor; Thirunavukarasu, Kalaivani; Ismail, Ismayadi; Rahman, N. A.; Hajalilou, Abdollah (JOCPR, 2014)
Microwave energy is highly efficient for heating and processing ceramic materials. Microwave sintering of doped barium strontium ceramics led to higher densification and the fine microstructure and improved magnetic properties. Effects of the substituted amount of Ni2+ and Co2+ on structure and magnetic properties of Ba0.5Sr0.5Fe12-xNixCoxO19 compounds have been systematically investigated by X-ray diffraction (XRD), high resolution scanning microscope (HR-SEM) and vibrating sample magnetometer (VSM). In our results, the suitable amount of Ni2+–Co2+ substitution slight decreased saturation magnetization. For Substitution of Ni-Co content of x≤0.4 the saturation magnetization varied from a range of 60.58 to 63.59 Am2/kg and while coercivity decreased from 805.37 to 280.28 Gauss respectively.